Poor treatment outcomes of children on highly active antiretroviral therapy: Protocol for a systematic review and meta-analysis - Atalell, K.A.; Alene, Kefyalew (BMJ PUBLISHING GROUP, 2020)
Introduction: While access to highly active antiretroviral therapy (HAART) for children with HIV has expanded and the use of HAART has substantially reduced the morbidity and mortality of children due to HIV, poor treatment outcomes among children with HIV are still a major public health problem globally. The aim of this systematic review and meta-analysis is to quantify treatment outcomes among children with HIV.